Exploring Student Subjectivity in Perceiving Courses Content in the Biology Department at an Islamic Religious University : (Penelusuran Subyektivitas Persepsi Mahasiswa dalam Mencerna Materi Mata Kuliah Jurusan Biologi di Perguruan Tinggi Agama Islam) - Pontiara, Pontiara; Ferry, Dharma; Damni, Albertos (Program Studi Pendidikan Biologi FKIP Universitas Jambi, 2023)
Individual interpretations of specific phenomena exhibit a wide range of variations. Some consider higher education to be of utmost importance, while others assert that it is merely a financial burden. Similar perspectives apply to the comparison between science and religion. These interpretations are influenced by the individual's background conducting the assessment and the specific context applied in that evaluation. Likewise, within the context of academic coursework, there is a diversity of opinions regarding the level of difficulty, often dependent on the student's understanding and subjective perspective of the course. This study aims to comprehend and analyse how students majoring in Biology subjectively interpret and perceive their Biology courses. The research employs a qualitative approach using the Grounded Theory methodology. The sample consists of 40 students selected through theoretical sampling. Data collection is conducted via a Google Form-based questionnaire. Some perceive introductory Biology courses as relatively easy, while courses involving calculations are often regarded as the most challenging. Interpretasi individu terhadap fenomena tertentu memiliki cakupan yang sangat bervariasi. Beberapa menganggap pendidikan tinggi sangat penting, sementara yang lain mengklaim bahwa itu hanya merupakan pemborosan uang. Pandangan serupa juga berlaku untuk perbandingan antara ilmu pengetahuan dan agama. Interpretasi ini dipengaruhi oleh latar belakang individu yang mengevaluasinya dan konteks spesifik yang diterapkan dalam evaluasi tersebut. Demikian juga, dalam konteks mata kuliah, ada keragaman pendapat mengenai tingkat kesulitan, yang sering kali bergantung pada pemahaman dan perspektif subjektif dari mahasiswa yang mengikuti mata kuliah tersebut. Penelitian ini bertujuan untuk memahami dan menganalisis cara mahasiswa jurusan Biologi mengartikan dan mempersepsikan mata kuliah Biologi secara subjektif. Penelitian ini menerapkan pendekatan kualitatif dengan menggunakan metode Grounded Theory. Sampel terdiri dari 40 mahasiswa yang dipilih dengan metode sampling teoritis. Pengumpulan data dilakukan melalui kuesioner berbasis Google Form. Beberapa menganggap mata kuliah Biologi tingkat dasar sebagai mata kuliah yang relatif gampang, dan mata kuliah yang melibatkan hitungan dianggap paling sulit. Â